(untitled) (Bangladesh Journal of Neuroscience, 2014)
Aim & background: As significant electrophysiological changes are found in asymptomatic neuropathy in diabetes mellitus and electrophysiological studies of nerve conduction velocity are our most sensitive tools to quantify early abnormalities, therefore, we tried to find out status of asymptomatic peripheral nerve dysfunction in recently diagnosed diabetic patients in Bangladesh perspective. Method :This study was carried out at BSMMU and BIRDEM during November 2005 and April 2006. The study included 60 subjects, 30 recently diagnosed diabetic subjects (14 male, 16 female). None had neuropathic symptoms or signs. All cases were selected randomly diagnosed by ADA criteria accepted by WHO. Thirty healthy controls with mean age comparable to that of diabetic subject were selected from the friends of the subjects and patients attending neurology outdoor of BSMMU. Result:Findings (mean±SD) were (case and control, respectively): Tibial nerve, DML 4.05±0.81 and 3.84±0.70 msec (P>0.10), CMAP 16.90±5.14 and 19.49±4.73 mV (P<0.05), MCV 45.43±4.55 and 48.24±4.72 m/ s (P<0.05), and F latency 45.09±12.43 and 42.50±8.93 msec (P>0.10); peroneal nerve, DML 4.12±1.10 and 4.03±0.67 msec (P>0.50), CMAP 5.80±2.89 and 6.97±1.79 mV (P>0.05), MCV 43.10±8.89 and 48.27±3.56 m/s (P<0.01), and F latency 50.27±10.81 and 41.32±3.05 msec (P<0.001); median nerve, DML 3.57±0.46 and 3.55±0.52 msec (P>0.50), CMAP 16.33±4.24 and 17.84±3.73 mV (P>0.10) and MCV 55.16±5.33 and 57.70±4.33 m/s (P<0.05), and F latency 25.08±5.28 and 24.39±4.83 msec (P>0.50); and ulnar nerve DML 2.57±0.33 an 3.17±0.61 msec (P<0.001), CMAP 14.65±3.32 and 17.29±6.83 mV (P>0.05), MCV 55.74±5.00 and 58.50±5.13 m/s (P<0.05), F latency 25.09±5.35 and 25.82±3.33 msec (P>0.50); sural nerve, DSL 2.46±0.68 and 3.12±0.45 msec (P<0.001), SNAP 19.44±10.25 and 25.32±7.88 ìV (P<0.05), SCV 49.95±10.22 and 52.46±3.96 m/s (P>0.10); median nerve, DSL 2.52±0.39 and 2.77±0.49 msec (P<0.05), SNAP 30.23±12.79 and 31.69±11.02 ìV (P>0.50), and SCV 56.90±6.77 and 57.41±5.85 m/s (P>0.50); and ulnar nerve, DSL 2.03±0.39 and 2.48±0.49 msec (P<0.001), SNAP 29.30±14.36 and 30.72±10.76 ìV (P>0.50), and SCV 60.96±8.38 and 57.93±7.15 m/s (P>0.10). Mean (±SD) HbA1c was significantly high (P<0.001) in case group (7.10±0.80%) compared to control (5.51±0.65%). Mean (±SD) SGPT showed no significant difference between case (36.10±13.02 u/L) and control (36.20±7.94 u/L). Similarly, mean (±SD) total cholesterol also showed no significant difference between case (201.57±37.56 mg/dl) and control (191.00±17.17 mg/dl). Conclusion: Motor nerve conduction parameters are affected more than sensory nerves and F-wave latencies are more frequently and early involved in these subjects. Abnormalities on nerve conduction was started in the feet rather than the hands.Clinical spectrum of diabetic neuropathy is variable and may be asymptomatic, but once established as polyneuropathy, it is irreversible and may finally be disabling. Early detection of diabetic neuropathy is one of the major goals in the management of diabetes since timely intervention may substantially reduce mortality and morbidity. Bangladesh Journal of Neuroscience 2014; Vol. 30 (1): 16-22